METHODOLOGY FOR ACCURATE ASSESSMENT OF PUPILS IN SECONDARY GENERAL EDUCATION INSTITUTIONS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explores the development of a comprehensive methodology for assessing pupils in secondary general education institutions. Emphasizing fairness, accuracy, and inclusivity, the methodology encompasses a range of assessment practices, including formative assessments to guide instruction and summative evaluations to measure overall achievement. By implementing this methodology, secondary education institutions can foster a supportive learning environment conducive to student growth and success.